Acute mesenteric ischemia (clinical cases) - L. K. Kulikov; Y. A. Privalov; A. L. Mikhaylov; A. V. Kalinichenko; V. F. Sobotovich; A. A. Smirnov (Acta Biomedica Scientifica, 2016)
Acute mesenteric ischemia is one of the most severe pathological conditions in terms of its course and prognosis. In the case of bowel infarction it is accompanied by an extremely high fatality rate. At the present day, despite there are ways to determine the patency of the vascular bed of the intestine accurately, developed principles and methods for the treatment of surgical interventions in different variants of acute occlusion of mesenteric vessels, it is not always possible to save the lives of patients with this disease. However, knowledge of the clinical picture of the disease, the consistent implementation of objective methods of diagnosis, timely decision on the need for surgical treatment can restore blood flow in the basin of the superior mesenteric artery and provide recovery and rehabilitation of these patients.